The systematic distribution of vascular epiphytes - a critical update - Zotz, Gerhard (Botanical journal of the Linnean Society, 2013)
Vascular epiphyte species exclusively, or at least primarily, germinate and grow on other plants without contact with the soil and, in contrast to mistletoes, without parasitizing their hosts. The last review of the systematic distribution of this diverse group of plants dates back more than two decades. The present study pursues three major goals: (1) it critically discusses conceptual problems arising from the distinction of epiphytes from non‐epiphytes; (2) it presents a compilation of epiphytic diversity derived from a vast number of sources; and (3) it arranges epiphyte diversity in an up‐to‐date taxonomic framework. The resulting compilation, which identifies 27 614 species of vascular epiphytes (including primary hemiepiphytes) representing 913 genera in 73 families, or approximately 9% of extant vascular plant diversity, is meant to be an important tool for studies on the ecology and evolution of epiphytes, but also for comparative studies with a focus on other life forms. © 2013 The Linnean Society of London